Pengaruh Efektivitas Sistem Informasi Akuntansi Terhadap Kualitas Laporan Keuangan Pada KSP Credit Union Tuke Jung - Yoseph Stefanus (BADAN PENERBIT STIEPARI PRESS, 2023)
This study aims to determine whether the effectiveness of accounting information systems affects the quality of financial reports at KSP Kopdit Tuke Jung. The type of research used is quantitative descriptive research. The population in this study were all KSP Kopdit Tuke Jung management, with a sampling technique using a saturated sample so that the total sample in this study was 53 people. Data analysis technique using simple linear regression. The data used in this study are primary data and secondary data using a data collection method, namely a questionnaire. Data processing in this study uses the SPSS (Statistica Package for the Social Sciences) software program. The results in this study indicate that the effectiveness of the accounting information system (X) has no effect on the quality of financial reports (Y).